When Genome-Based Approach Meets the “Old but Good”: Revealing Genes Involved in the Antibacterial Activity of Pseudomonas sp. P482 against Soft Rot Pathogens - Krzyżanowska, Dorota M.; Ossowicki, Adam; Rajewska, Magdalena; Maciąg, Tomasz; Jabłońska, Magdalena; Obuchowski, Michał; Heeb, Stephan; Jafra, Sylwia (Frontiers in Microbiology, 2016)
Dickeya solani and Pectobacterium carotovorum subsp. brasili¬ense are recently established species of bacterial plant pathogens causing black leg and soft rot of many vegetables and ornamental plants. Pseudomonas sp. strain P482 inhibits the growth of these pathogens, a desired trait considering the limited measures to combat these diseases. In this study, we determined the genetic background of the antibacterial activity of P482, and established the phylogenetic position of this strain. Pseudomonas sp. P482 was classified as Pseudomonas donghuensis. Genome mining revealed that the P482 genome does not contain genes determining the synthesis of known antimicrobials. However, the ClusterFinder algorithm, designed to detect atypical or novel classes of secondary metabolite gene clusters, predicted 18 such clusters in the genome. Screening of a Tn5 mutant library yielded an antimicrobial negative transposon mutant. The transposon insertion was located in a gene encoding an HpcH/HpaI aldolase/citrate lyase family protein. This gene is located in a hypothetical cluster predicted by the ClusterFinder, together with the downstream homologues of four nfs genes, that confer production of a nonfluorescent siderophore by P. donghuensis HYST. Site-directed inactivation of the HpcH/HpaI aldolase gene, the adjacent short chain dehydrogenase gene, as well as a homologue of an essential nfs cluster gene, all abolished the antimicrobial activity of the P482, suggesting their involvement in a common biosynthesis pathway. However, none of the mutants showed a decreased siderophore yield, neither was the antimicrobial activity of the wild type P482 compromised by high iron bioavailability. A genomic region comprising the nfs cluster and three upstream genes is involved in the antibacterial activity of P. donghuensis P482 against D. solani and P. carotovorum subsp. brasiliense. The genes studied are unique to the two known P. donghuensis strains. This study illustrates that mining of microbial genomes is a powerful approach for predicting the presence of novel secondary-metabolite encoding genes especially when coupled with transposon mutagenesis.